Cancer chemoprevention research with selenium in the post-SELECT era: Promises and challenges. (2nd January 2016) - Lü, Junxuan; Zhang, Jinhui; Jiang, Cheng; Deng, Yibin; Özten, Nur; Bosland, Maarten C.
Abstract : The negative efficacy outcomes of double-blinded, randomized, placebo-controlled Phase III human clinical trials with selenomethionine (SeMet) and SeMet-rich selenized-yeast (Se-yeast) for prostate cancer prevention and Se-yeast for prevention of nonsmall cell lung cancer (NSCLC) in North America lead to rejection of SeMet/Se-yeast for cancer prevention in Se-adequate populations. We identify 2 major lessons from the outcomes of these trials: 1) the antioxidant hypothesis was tested in wrong subjects or patient populations, and 2) the selection of Se agents was not supported by cell culture and preclinical animal efficacy data as is common in drug development. We propose that next-generation forms of Se (next-gen Se), such as methylselenol precursors, offer biologically appropriate approaches for cancer chemoprevention but these are faced with formidable challenges. Solid mechanism-based preclinical efficacy assessments and comprehensive safety studies with next-gen Se will be essential to revitalize the idea of cancer chemoprevention with Se in the post-SELECT era. We advocate smaller mechanism-driven Phase I/II trials with these next-gen Se to guide and justify future decisions for definitive Phase III chemoprevention efficacy trials.